Exploring quality of life among elderly persons living with HIV in Accra, Ghana - Marijanatu Abdulai; Philip Teg-Nefaah Tabong; Harriet Affran Bonful; Adolphina Addo-Lartey; Bismark Sarfo (PLoS ONE, 2025)
Introduction The introduction and rapid scale-up of AntiRetroviral Treatment (ART) has contributed to a significant reduction in HIV-associated morbidities and mortalities, resulting in increasing life expectancy. Ageing with HIV presents several challenges which affect peoples’ well-being and quality of life (QoL). Despite this, there is scarcity of research on the QoL of Elderly Persons Living with HIV (EPLHIV) in Sub-Saharan Africa (SSA), particularly in Ghana. This study, therefore, examines the QoL of the elderly population using a qualitative approach. Methods A purposive sampling method was used to select eight (8) participants for Key Informant Interviews (KIIs) and twenty-nine (29) participants for Focus Group Discussions (FGDs). In all, eight (8) KIIs with stakeholders and four (4) FGDs with EPLHIV were used to collect data for this study. Both the KIIs and FGDs interview guides addressed the four domains of the WHO’s Quality of Life (WHOQoL) Bref assessment tool; physical, psychological, social, and environmental health with the overall focus on evaluating quality of life. The data was analysed thematically using QSR NVivo 11. Results Of the 37 participants, majority (54%) of them were females, and a considerable proportion (94%) had attained formal education. The most prolonged duration of persons living with HIV among the respondents was 25 years. Four main themes were identified: physical health, social well being, environmental health, and psychological health. The study further revealed that EPLHIV reflect on their condition, face the dilemma of disclosing their status, are confronted with inadequate privacy for health care, wait long in the queue at the health facilities to be attended to, and have no focused or tailored HIV services for the EPLHIV and experiences worsened physical conditions. Conclusions The study’s findings shed light on the quality of life among EPLHIV, offering new evidence. Consequently, some of the conditions related to the various domains such as stigma, delay in receiving health care could negatively influence the QoL of EPLHIV. To improve the QoL of EPLHIV, it is imperative to implement specialized services tailored to the unique needs of EPLHIV. Additionally, healthcare workers at ART clinics should receive training in psychological and geriatric care counseling, considering the increasing life expectancy of EPLHIV. There should be counseling sessions on disclosure and non-disclosure to help those who want to disclose their status do so.